Pelatihan Aplikasi Anggaran Kerja Berbasis Website Guna Menentukan Rencana Kerja Anggaran Pembangunan Desa - Muhamad Awiet Wiedanto Prasetyo; Gustin Setyaningsih; Afilda Trisetya Riziana; Sabrina Uhti Kusreynada; Dhewanda Putro Laksono (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The Village government and village instituions formulate a development program or Village Development Work Plan (RKPDes) as an elaboration of the Village Metium Term Plan (RJPMDes). In this case, determining development work in a village still has several problems because there is no common ground in what development plans should be prioritized. The village government still makes decisions by way of decliberation with the village absence of certain aspects to be taken into consideration. A mechanism for determining work programs in a village using a way of receiving proposals or aspirations from the community from the level of the neighbourhood unit then the next hamlet level at a village meeting. From the deliberation process there are still decisions because they do not consider the needs or benefits that will be obtained by the community. Starting with the collection of observation data, interviews and literature study. The head of the Amikom Mitra Masyarakat team conducted interviews with village heads and village officials to find out the problems that existed in the community, then sampled the community as interview respondents and obtained information on the mechanism for compiling a work plan and how to formulate these problems that could be solved with a touch of information technology. Then the team looked for references in the form of research and service journal literature with the theme of the Village Development Work Plan. The nest stage is for team members to prepare aplications to be socialized by the village head and village officials, the head of the BPD and its members, PKK, head of RT RW, Karang Taruna, Linmas and local community leaders